The Implementation of Artificial Intelligence in Islamic Education Learning at Elementary School - Najla Kamilia Marwa; Saepul Anwar; Mokh. Iman Firmansyah (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
The rapid development of technology, especially in the twenty-first century driven by the exponential increase in artificial intelligence (AI) technology, has led humans to a new era that offers a variety of conveniences in various fields, including education. This study aims to analyze the practice of using AI in Islamic Education learning in schools, especially in elementary schools. The method used in this research is a qualitative method using a descriptive approach with purposive sampling as a reference for data collection to determine the use of artificial intelligence in Islamic Education learning. Respondents taken were Islamic Education teachers who have used AI in their learning with one year of experience and understand and use Artificial Intelligence both during planning and during learning. The results of the study found that the use of AI in the field of education is increasingly common in Indonesia. This is due to the support from the Education Department in conducting training on the use of AI, especially Gemini AI in schools. Teachers have also integrated AI into Islamic Education learning by using AI at every stage of learning, starting from creating modules, learning media, powerpoints, questions, quizzes, learning materials and many more. In conclusion, AI has been used in the teaching and learning process, especially in Islamic Education learning at school.